Do turloughs occur in Slovenia? - Sheehy Skeefington, Micheline; Scott, Nick E. (Acta Carsologica, 2008)
Micheline Shehy Skeffington & Nick. E. Scott: Do turloughs occur in Slovenia? Turloughs are karst basins that fill seasonally with mostly groundwater and drain, usually in summer, to reveal a sedge or grassland community. They are often described as being virtually unique to Ireland. The much larger seasonal poljes of the Slovenian karst are considered different to turloughs. However, a series of small temporary karst lakes in the Slovenian Pivka valley seem remarkably similar to Irish turloughs. Like turloughs, they fill and empty largely through estavelles connecting to underground water systems, which rise and fall with high seasonal rainfall. The Slovenian sites, however, support less wetland communities than Irish turloughs, probably due to drier summer conditions. The plant communities of both systems occur in zones around the basin, related to flood duration. Relevés taken at five Slovenian sites revealed that Petelinjsko jezero, which floods longest each year, is the most similar to turloughs, with, in the lower basin, Eleocharis palustris, potentilla reptans and the unusual form of Ranuculus repens commonly found in Irish turloughs. The difference in climate and terrain means that the Slovenian sites are managed for hay or silage, while the Irish turloughs are under pasture. However, for both, regular flooding precludes much agricultural improvement, so that they are now refuges for flora and fauna. A revised definition for turloughs is proposed and a case made for these Slovenian wetland systems to be recognised as turloughs and for the EU Habitats Directive to be amended to include poljes and other similar temporary karst wetland systems as well as turloughs.